Optimization of Vegetative Stage of Baby Cucumber (Cucumis sativus L. Var. Marta) using the Genetic Algorithm - Tamrin .; K. B. Seminar; H. Suhardiyanto; S. Hardjoamidjojo (Jurnal Keteknikan Pertanian, 2005)
An  optimization was conducted to a growth model for baby cucumber (Cucumis sativus L. Var. Marta). The model gives information of nutrient intake and micro climate conditions (temperature, humidity, and irrediation) to get response of the plant (ratio of canopy area and stem diameter) and the loss of nutrient solution. The model ws then coupled with genetic algoritm in order to get optimum result efficiently. Two fitness functions were used in the application og genetic algoritm. The result showed that the first fitness function could be used to optimize the plant response (ratio of canopy area and stem diameter) and the loss of nutrient solution efficiently as indicated by the maximum fitness value (Pc = 0.6 and Pm = 0.01).